Cultural dimension issues in Indonesia human resource management practices: a structured literature review - Novianti, Khusnul Rofida (Faculty of Economics, State Islamic University of Maulana Malik Ibrahim Malang, 2018)
Indonesia has a complex culture that is distinct from other Asian countries. Indonesian is an emerging market and managing Indonesian people is not easy. This is because of the complexity of culture, ethnic, religion, geographic, historic, economic and politic system. Cultural issues is a vital aspect in collectivist country like Indonesia before decided HRM policy. This paper has aim to determine cultural dimension issues based on Hofstede national culture and GLOBE project (Global Leadership and Organisational Behaviour Effectiveness) on Indonesia human resource management practices using SLR (Structured Literature Review) approach. This paper provides insights related to the Indonesia human resources management practice (recruitment and selection, training development and rewards, compensation, performance appraisal and industrial relation).